An experimental study on the aerodynamic performance of flexible tandem wings - Zheng, Yingying (2016)
As typical four-wing insects, the dragonflies have the features of both flexible wing and tandem-wing configuration. In previous studies, these two features have been widely studied and proven to account much for the great flight capability of the dragonflies. However, these two features were usually concerned separately. How the flexibility will affect the performance of tandem wings, and how tandem-wing configuration will affect the performance of flexible wings are still unknown. Therefore, the present work aims to study the combined effects of the wing flexibility and tandem configuration by investigating the aerodynamic performance of flexible tandem wings. Three sets of dragonfly-like flexible tandem wings termed Wing I, Wing II and Wing III, and a set of rigid tandem wings as references were investigated in a hovering and two forward flights (St = 0.3 and 0.6). Three phase differences between the forewing and hindwing, i.e. 0°, 90° and 180°, were employed. The results of force measurements showed that both the flexibility and phase difference had significant effects on the aerodynamic performance of flexible tandem wings. Generally, the tandem Wing III models with appropriate flexibility outperformed the other tandem wing models. The most favorable phase difference for different wing models varied. According to deformation measurements, the bending deformation of flexible wings was found to cause lags of wings’ locations in plunging direction as compared to the rigid wings. Both phase-locked PIV and time-resolved PIV measurements were carried out. Comparing the flow fields of Wing III models and rigid tandem wings, the lags contributed to the force generation of Wing III models by making the LEVs closer to the wings. Besides, the lags restrained the shedding of LEVs on the Wing III models as compared to that on the rigid wings, which also offered benefits to the Wing III models. What is more important, the lags modified the separation between forewing and hindwing, which resulted in different forewing-hindwing interactions between the tandem Wing III models and tandem rigid wings.